Amperometric biosensor for glucose detection based-on immobilisation of glucose oxidase in acetic cellulose membrane using ferrocene as mediator - Asnawati Asnawati; Dwi Indarti; Tri Mulyono; Gembong Kesuma B (Jurnal ILMU DASAR, 2013)
The study reported the development of glucose ampherometric biosensor based on immobilization of glucose oxidase on cellulose acetate membrane with ferrocene as a mediator. Biosensor was designed with model Fc, GOx, CP / GOx / CA where ferrocene and the enzyme glucose oxidase on carbon paste in immobilizatin on the electrode body in the form of glass tubes and in other parts of the enzyme glucose oxidase in immobilizatin on cellulose acetate membrane with adsorption techniques are placed in electrode tip by using the o-ring. The presence of enzymes immobilization was determined quantitatively by enzyme immobilization was Km value. The results showed the composition of acetone-water in the optimum coagulation bath is 0:100% and 0,0008 g of Optimum ferrocene. Biosensor for measuring glucose in the area amperometri 0,1 to 3 mM with regression coefficient of 0,996, the detection limit of 0,01 mM, sensitivity of 0,989 μA / mM, the reproducibility of 0,07 to 0,3% and lifetime of 1 day. Keywords : Biosensor; glucose oxidase ; acetic cellulose; Ferrocene: Ampherometric.